EFFECT OF AUDIT QUALITY AS A MODERATOR BETWEEN MANAGERIAL OWNERSHIP, LEVERAGE, FREE CASH FLOW, AND PROFITABILITY ON EARNINGS MANAGEMENT - Rosyidah, Nida'ur; Rahayu, Ruci Arizanda (Berkala Akuntansi dan Keuangan Indonesia, 2024)
This study aims to determine whether audit quality can moderate the relationship between managerial ownership, leverage, free cash flow, and profitability on earnings management. The research was conducted on food and beverage sub-sector companies listed on the Indonesia Stock Exchange for 2017-2021 by looking at financial reports through the IDX website at the Muhammadiyah University of Sidoarjo Investment Gallery and obtained a total sample of 65 companies. This type of research is quantitative research with sampling using purposive sampling technique. The analysis technique uses the Moderated Regression Analysis (MRA) Test with SPSS software. The results of this study indicate that managerial ownership, profitability, and free cash flow have an effect on earnings management, while leverage has no effect on earnings management. The results of moderation indicate that audit quality is able to moderate the relationship between free cash flow and earnings management, but audit quality is not able to moderate the relationship between managerial ownership, leverage, and profitability on earnings management.